2020
DOI: 10.18632/aging.103310
|View full text |Cite
|
Sign up to set email alerts
|

Clusterin exerts a cytoprotective and antioxidant effect in human osteoarthritic cartilage

Abstract: Osteoarthritis (OA) is the most common joint disease characterized by destruction of articular cartilage. OA-induced cartilage degeneration causes inflammation, oxidative stress and the hypertrophic shift of quiescent chondrocytes. Clusterin (CLU) is a ubiquitous glycoprotein implicated in many cellular processes and its upregulation has been recently reported in OA cartilage. However, the specific role of CLU in OA cartilage injury has not been investigated yet. We analyzed CLU expression in human articular c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 52 publications
(81 reference statements)
0
12
0
Order By: Relevance
“…The epidermal growth factor receptor (EGFR) system plays important roles in multiple processes, such as the differentiation and proliferation of osteoclasts, osteoblasts and chondrocytes [ 63 ]. Both beta-arrestin-2 (ARRB2) and clusterin (CLU) could inhibit the inflammatory response of chondrocytes, but CLU could also influence the proliferation and differentiation of chondrocytes [ 64 , 65 ]. In this study, we found that the expression of Cxcl13, Chad, Arrb2, Fgf9, Egfr and Clu was obviously suppressed in rats with CIA, but WB treatment increased it to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…The epidermal growth factor receptor (EGFR) system plays important roles in multiple processes, such as the differentiation and proliferation of osteoclasts, osteoblasts and chondrocytes [ 63 ]. Both beta-arrestin-2 (ARRB2) and clusterin (CLU) could inhibit the inflammatory response of chondrocytes, but CLU could also influence the proliferation and differentiation of chondrocytes [ 64 , 65 ]. In this study, we found that the expression of Cxcl13, Chad, Arrb2, Fgf9, Egfr and Clu was obviously suppressed in rats with CIA, but WB treatment increased it to a certain degree.…”
Section: Discussionmentioning
confidence: 99%
“…The levels of COMP, a cartilage degradation marker, in the explant secretome were increased two-fold under IL-1β and TNF-α stimulation versus the control. In contrast to the above results, human OA articular chondrocytes cultured in vitro were reported to express higher CLU mRNA and protein levels (detected in total cell lysates) compared to untreated controls [ 12 ] We propose that lower sCLU secretion by OA cartilage could be caused by an interruption at the transcriptional level, or by CLU being retained intracellularly during stress, rather than by degradation of extracellular sCLU.…”
Section: Clu As a Translational Biomarker Of Oamentioning
confidence: 86%
“…Inflammation in OA is different from rheumatoid arthritis (RA), psoriatic arthritis (PsA), and other autoimmune joint diseases – it is defined as low-grade inflammation but chronic and persistent [ 9 , 10 ]. All of these changes occurring over time lead to joint destruction, pain, and functional disability [ 11 , 12 ]. The mechanisms and pathways involved in the pathogenesis and progression of OA are not fully understood but senescence [ 13 ], abnormal mechanical load [ 14 ], metabolic dysfunction [ 15 , 16 ], and low-grade inflammation [ 10 , 17 ] are all thought to be important contributing factors.…”
Section: Introductionmentioning
confidence: 99%
“…The results showed significantly increased expression of CLU in LF samples; however, there was no marked difference in CLU levels in blood samples from the LFH group and non-LFH group. CLU upregulation has been reported in local tissue, such as OA-induced cartilage degeneration 38 , osteoporotic disease 39 , tears of dry eye 19 and brain tissues of AD patients. The results suggested specifically high expression of CLU in LF tissues prone to fibrosis.…”
Section: Discussionmentioning
confidence: 99%